Effect of telluric acid addition on thermal behavior of cesium dihydrogen phosphate - Beyribey, Berceste; Gunay, Emre; Saygi, Berrin; Corbacioglu, Burcu; Sarac, Hanifi (IOS PRESS, 2016)
xCsH(2)PO(4)center dot(1-x)Te(OH)(6) composites have been synthesized for the different compositions, x = 0.02, 0.04, 0.05, 0.06, 0.08 (labeled composites A-E). The composites were characterized by Scanning Electron Microscopy (SEM), X-Ray Diffraction (XRD), Thermogravimetry (TG) and Differential Thermal Analysis (DTA). Telluric acid, Te(OH) 6, added to cesium dihydrogen phosphate (CsH2PO4) significantly effects the structure, particle size and thermal stability of the composite material. Enhanced thermal stability could lead to use of CsH2PO4 as an electrolyte in low temperature fuel cells.
Keywords: Solid acids; low temperature fuel cells; composite materials; amorphous materials; CSH2PO4; COMPOSITES; Chemistry